Ecological benefits of artificial vegetation restoration on local climate condition in abandoned mining area - Aishajiang Aili; Zhang Yuguang; Lin Tao; Xu Hailiang; Fabiola Bakayisire; Abdul Waheed; Zhang Qin (Ecological Indicators)
The abandoned mining area in Hami, Xinjiang, suffers from severe ecological degradation, necessitating urgent vegetation restoration to improve local climate conditions. This study examines the ecological benefits of artificial re-vegetation conducted by our team since 2021. Using the Hybrid Single-Particle Lagrangian Integrated Trajectory model (HYSPLIT) backward trajectory model and Global Data Assimilation System (GDAS) meteorological data, the long-range movement paths of air masses reaching the study area were identified. Simultaneously, on-site monitoring of meteorological factors (air temperature and humidity) was conducted to compare differences between the control point (non-vegetated area) and the artificially vegetated area. Additionally, wind speeds were monitored on both the windward and leeward sides of the vegetation restoration area for 66 days. Wind directions perpendicular to vegetation, to assess windbreak efficiency. The results indicated that the HYSPLIT model and the K-means clustering technique classified air masses’ long-range transportation into three categories: NW, N, and ES clusters. This classification illustrated the impact of regional climatic systems on local conditions. It showed cooler and more humid air masses from the northwest contributing significantly to local climate improvements. In the restored areas, high vegetation coverage and height significantly reduced air temperature by up to 1.5 °C and increased humidity by 2.7 % compared to the control area. Windbreak efficiency was notably enhanced, with wind speeds at 0.5 to 1 m heights on the leeward side reduced by approximately 1.2–1.7 m/s. This study underscores the critical role of artificial vegetation restoration in mitigating mining activities’ adverse effects, improving local climatic conditions, and promoting sustainable ecological rehabilitation in arid regions. The findings provide valuable insights for future ecological restoration projects and sustainable environmental management in similar degraded landscapes.